The effects of L-carnitine supplementation on glycemic markers in adults: A systematic review and dose-response meta-analysis - Zamani, Mohammad; Pahlavani, Naseh; Nikbaf-Shandiz, Mahlagha; Rasaei, Niloufar; Ghaffarian-Ensaf, Rasool; Asbaghi, Omid; Shiraseb, Farideh; Rastgoo, Samira (Frontiers in Nutrition, 2023)
Background and aims Hyperglycemia and insulin resistance are concerns today worldwide. Recently, L-carnitine supplementation has been suggested as an effective adjunctive therapy in glycemic control. Therefore, it seems important to investigate its effect on glycemic markers. Methods PubMed, Scopus, Web of Science, and the Cochrane databases were searched in October 2022 for prospective studies on the effects of L-carnitine supplementation on glycemic markers. Inclusion criteria included adult participants and taking oral L-carnitine supplements for at least seven days. The pooled weighted mean difference (WMD) was calculated using a random-effects model. Results We included the 41 randomized controlled trials (RCTs) (n = 2900) with 44 effect sizes in this study. In the pooled analysis; L-carnitine supplementation had a significant effect on fasting blood glucose (FBG) (mg/dl) [WMD = −3.22 mg/dl; 95% CI, −5.21 to −1.23; p = 0.002; I2 = 88.6%, p < 0.001], hemoglobin A1c (HbA1c) (%) [WMD = −0.27%; 95% CI, −0.47 to −0.07; p = 0.007; I2 = 90.1%, p < 0.001] and homeostasis model assessment-estimate insulin resistance (HOMA-IR) [WMD = −0.73; 95% CI, −1.21 to −0.25; p = 0.003; I2 = 98.2%, p < 0.001] in the intervention compared to the control group. L-carnitine supplementation had a reducing effect on baseline FBG ≥100 mg/dl, trial duration ≥12 weeks, intervention dose ≥2 g/day, participants with overweight and obesity (baseline BMI 25–29.9 and >30 kg/m2), and diabetic patients. Also, L-carnitine significantly affected insulin (pmol/l), HOMA-IR (%), and HbA1c (%) in trial duration ≥12 weeks, intervention dose ≥2 g/day, and participants with obesity (baseline BMI >30 kg/m2). It also had a reducing effect on HOMA-IR in diabetic patients, non-diabetic patients, and just diabetic patients for insulin, and HbA1c. There was a significant nonlinear relationship between the duration of intervention and changes in FBG, HbA1c, and HOMA-IR. In addition, there was a significant nonlinear relationship between dose (≥2 g/day) and changes in insulin, as well as a significant linear relationship between the duration (weeks) (coefficients = −16.45, p = 0.004) of intervention and changes in HbA1C. Conclusions L-carnitine could reduce the levels of FBG, HbA1c, and HOMA-IR. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier: CRD42022358692.